2023
DOI: 10.1371/journal.pone.0285049
|View full text |Cite
|
Sign up to set email alerts
|

Strengthened social ties in disasters: Threat-awe encourages interdependent worldviews via powerlessness

Abstract: Threat-awe, a negatively valenced variant of awe, is thought to strengthen social ties among community members. However, few empirical studies have examined the social functions of threat-awe. This study investigated whether threat-awe is linked to interdependent worldviews through feelings of powerlessness in comparison with positive awe. After remembering and describing their experiences of positive-or threat-awe, 486 Japanese participants reported on items regarding a small self, a sense of powerlessness, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Previous studies suggested that feelings of awe that are triggered by threatening stimuli such as natural disasters could be tinged with the perception of threat ( Takano & Nomura, 2022b ). Given that even the recollection of awe experiences based on examples that do not include negative elements (e.g., seeing aurora) evokes the feelings of ifu , negative awe in Japanese ( Takano & Nomura, 2023a ), Japanese people might be more likely to feel threatened during awe experiences due to Japan’s geographic and historical background.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggested that feelings of awe that are triggered by threatening stimuli such as natural disasters could be tinged with the perception of threat ( Takano & Nomura, 2022b ). Given that even the recollection of awe experiences based on examples that do not include negative elements (e.g., seeing aurora) evokes the feelings of ifu , negative awe in Japanese ( Takano & Nomura, 2023a ), Japanese people might be more likely to feel threatened during awe experiences due to Japan’s geographic and historical background.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the relationship between ikei and ifu, both of which are awe in Japanese, was more evident in the Koyasan condition than the Nachi condition. While ikei ("畏敬") involves respect or a positive evaluation as indicated by its second character "敬," ifu ("畏怖") conveys more negative feelings since the second character "怖" means being afraid (Takano & Nomura, 2023). Previous studies showed that ifu is used more frequently when describing awe experiences that involve threat (Takano & Nomura, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…While ikei ("畏敬") involves respect or a positive evaluation as indicated by its second character "敬," ifu ("畏怖") conveys more negative feelings since the second character "怖" means being afraid (Takano & Nomura, 2023). Previous studies showed that ifu is used more frequently when describing awe experiences that involve threat (Takano & Nomura, 2023). Thus, the feelings of awe during negative spiritual experiences might be associated with threat components more strongly.…”
Section: Discussionmentioning
confidence: 99%
“…In each model, we used temperature, humidity, and contrast-coding for the two emotion conditions (awe-contrast: awe = 2/3, amusement = − 1/3, neutral = − 1/3; amusement-contrast: awe = − 1/3, amusement = 2/3, neutral = − 1/3) as fixed effects with one random intercept for participants 9 . Regarding the physiological measurements, we examined whether there were effects of other emotions, habituation, or demographic heterogeneity because some previous studies have suggested that these factors may moderate the effects of awe 38 41 . We considered three models in addition to the simple models: control models, which controlled for the main effects of emotions other than awe that were elicited from the video (i.e., amusement and fear as general positive and negative emotions, respectively); order models, which included the interaction effects between the contrasts and the order in which the videos were presented within each emotion condition (first = − 1/2, second = 1/2); and demographic models with the interaction effects between awe-contrast and age and gender (the values of age were centered).…”
Section: Methodsmentioning
confidence: 99%